ALUMINIUM IN HIGH-MANGANESE STEEL - M. S. Shramko; S. P. Mihailov (Литьë и металлургия, 2006)
It is shown that for preventing of nitride-aluminium formation in high-manganese steel, the contents of aluminium up to 0,01% is expedient.